Case Study of Paranoid Schizophrenia in Young Adults - Putra, Hamzah; Desy Anggraeni (HM Publisher, 2024)
Introduction: An individual with paranoid schizophrenia exhibits a preoccupation with one or more delusions and experiences frequent auditory hallucinations. This study aimed to describe the diagnosis and treatment of paranoid schizophrenia in young men. Case presentation: A 20-year-old man was found sitting in the middle of traffic on a bustling route, prompting the cops to transport him to the emergency department for medical care. The patient showed poor personal hygiene during the mental health assessment, appearing dirty and untidy. He constantly paces the examining room, ensuring his back is always against the wall. He exudes a subtle sense of unease with his environment. He characterizes his demeanor as